Tortillitas para mama and other nursery rhymes : Spanish and English - Griego, Margot C.; Cooney, Barbara, 1917-2000. (New York : Holt, Rinehart and Winston, 1981)
A collection of nursery rhymes, each in both English and Spanish, collected from the Spanish community in the Americas, many with instructions for accompanying finger plays or other activities.
NP
Accelerated Reader
Keywords: Nursery rhymes, Spanish -- Juvenile literature; Finger play -- Juvenile literature; Cuentos en rima -- Literatura juvenil; Juegos infantiles con los dedos -- Literatura juvenil